Teach yourself visually Word 2013 - Marmel, Elaine J. (Teach yourself visually., 2013)
Provides clear, step-by-step instructions for tackling more than 160 Word 2013 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Word 2013 in no time.